2006
DOI: 10.3934/dcds.2006.14.295
|View full text |Cite
|
Sign up to set email alerts
|

Topological methods in the instability problem of Hamiltonian systems

Abstract: We use topological methods to investigate some recently proposed mechanisms of instability (Arnol'd diffusion) in Hamiltonian systems.In these mechanisms, chains of heteroclinic connections between whiskered tori are constructed, based on the existence of a normally hyperbolic manifold Λ, so that: (a) the manifold Λ is covered rather densely by transitive tori (possibly of different topology), (b) the manifolds W s Λ , W u Λ intersect transversally, (c) the systems satisfy some explicit non-degeneracy assumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 54 publications
(82 citation statements)
references
References 30 publications
2
80
0
Order By: Relevance
“…The approaches used in these works range from variational to geometric/topological. This paper is more in line with the geometric method developed in [21,32,31,33].…”
Section: Methodssupporting
confidence: 59%
See 1 more Smart Citation
“…The approaches used in these works range from variational to geometric/topological. This paper is more in line with the geometric method developed in [21,32,31,33].…”
Section: Methodssupporting
confidence: 59%
“…We mention that transition chains of level sets of the action also appear in [32], but they have not been numerically implemented before. Now we briefly explain the construction of transition chains of action level sets.…”
Section: Methodsmentioning
confidence: 99%
“…An interesting particular case is when the motion given by f 0 is integrable when restricted to the invariant manifold Λ = k 0 (N ). This situation occurs in the problems considered in [DLS00,DLS03,DLS06a,DLS06b,GL06a,GL06b]. In such a case, the dynamics by f 0 on Λ has a simple expression and one can carry the perturbation theory to all orders in ε less or equal than r. In those papers, one can find detailed perturbative formulas to order m ≤ r with error estimates.…”
Section: A Geometric Framework For a Perturbative Calculation Of The mentioning
confidence: 99%
“…The use of the scattering map was crucial for the applications in [DLS03,DLS06a,GL06a,GL06b]. In those papers, it was shown that the perturbative computations of the scattering map are a convenient improvement of the Melnikov method since they are geometrically natural.…”
Section: Introductionmentioning
confidence: 99%
“…Topological methods were previously applied to the Arnold diffusion problem in [35,28,21,23]. Transition chains of tori formed with topologically crossing heteroclinic connections were considered in [22].…”
Section: Marian Gidea and Clark Robinsonmentioning
confidence: 99%